Intermittent subocclusion due to cystic intestinal duplication - Aranda-Paniora, Franklin (2012)
Duplication of the intestinal tract is a rare anomaly and symptoms depend on size, location, and mucosal lining. We report a 2 year-old boy from Iquitos with cystic intestinal duplication found between the second and third portion of duodenum that produced intermittent partial intestinal obstruction.